Analysis of Topological and Geographical Multicast Routing Algorithms onWireless Ad Hoc Networks - Santos, R. A.; González, A.; Villaseñor, L.; García-Ruíz, M.; Range, V.; Edwars, A. (Elektronika ir Elektrotechnika, 2008)
Performance analysis of topological and geographical multicast routing algorithms for mobile wireless ad-hoc networks is presented. Flooding and On-Demand Multicast Routing Protocol (ODMRP) are simulated and compared with two novels protocols: Topological Multicast Routing (ToMuRo) and Geographical Multicast Routing (GeMuRo) in pedestrian and vehicular scenarios. The scenarios evaluated consider one multicast transmitter and one, two, and three multicast receivers under various mobility and transmission ranges. The behavior of 250 nodes is evaluated in terms of End to End Delay (EED), jitter, packet delivery ratio, and overhead. Results show that ToMuRo is suitable for pedestrian scenarios due to its tree-based architecture and GeMuRo is proper for vehicular scenarios because it is based on a mesh topology. Ill. 11, bibl. 13 (in English; summaries in English, Russian and Lithuanian).